Effect of dietary supplementation of ginger extract on growth, carcass characteristics and haematological parameters in broilers - Talukder, Sudipta; Hasan, Md Mehedi; Noman, Zakaria Al; Sarker, Yousuf Ali; Paul, Torun Kumar; Sikder, Mahmudul Hasan (Asian Journal of Medical and Biological Research, 2017)
This study evaluated the effect of ginger on the growth performance, carcass quality of broiler chickens. 20 broiler chickens were randomly selected into two treatment groups identified as T1 and T2 with a positive control and a negative control group. Each treatment contained with five birds. Birds on T1 were treated with 1% ginger extract and T2 was treated with 2% ginger extract via drinking water. Significant variations (p<0.05) existed between the control and other treatments in mean final body weight, dressed weight, daily feed intake and feed conversion ratio. At the end of experiment (35th day) for 1% ginger extraction treatment the live body weight is 1746gm (p<0.05), dressing weight 1106.4 (p<0.05) and FCR is 1.67(p<0.05). The usage of the test ingredients had a significant effect (p<0.05) on dressing percentage. Supplementation of ginger improves the performance of broilers when added at the rate of 1% of broiler ration and can be a possible alternative to antibiotic growth promoter in the feeding of broiler chicken. Asian J. Med. Biol. Res. June 2017, 3(2): 211-215